Pharmaceutical Pricing and Reimbursement Policies in Germany - Paris, Valérie (OECD Publishing, 2008)
This paper describes pharmaceutical pricing and reimbursement policies in Germany, considering them in the broader environment in which they operate, and assesses their impact on the achievement of a number of policy goals. Pharmaceutical coverage is comprehensive, with a high level of public funding, and ensures access to treatments. However, recent increases in out-of-pocket payments may impair affordability for the poorest part of the population. Germany does not regulate ex-manufacturer prices of pharmaceuticals at market entry (though distribution margins are regulated for reimbursed drugs). On the other hand, maximum reimbursement amounts (known as reference prices) are set for products which can be clustered in groups of equivalent (generic) or comparable products (...)
Keywords: Social Issues/Migration/Health; Germany